Desenvolvimento de um veículo aéreo não tripulado com sustentação e propulsão híbrida - Lucena, Alysson Nascimento de (2018)
This work aims to present the development of a double hybrid unmanned aerial vehicle (UAV), capable of reconciling the advantages of two types of aircraft (fixed wing and multirotor), using combustion and electric motors for propulsion and in flight support the wing and the multirotor, able to take off and land vertically, to perform slow or stopped flights, also to execute horizontal flight with support by the wing and propulsion by combustion engine that guarantees greater autonomy. In order to carry out this study, three aircraft were developed, initially a flying wing and a tricopter multirotor with the objective of analyzing separately each type of aircraft, after the tests and analyzes a double hybrid VANT was developed, a flying wing and a hexacopter, motor propulsion electrical and combustion. From the theoretical tests and calculations of the hybrid aircraft, the viability of a new type of aircraft, with its own characteristics, was able to reconcile the advantages of two types of aircraft.